2018
DOI: 10.3390/app8050664
|View full text |Cite
|
Sign up to set email alerts
|

DF Relayed Subcarrier FSO Links over Malaga Turbulence Channels with Phase Noise and Non-Zero Boresight Pointing Errors

Abstract: Subcarrier free-space optical (FSO) systems using coherent recovery techniques at the receiver have acquired growing research interest in recent times. However, their optimal performance is diminished by the non-perfect synchronization of carrier frequency and phase, which is mainly due to phase noise problems. Moreover, turbulence and pointing error effects further deteriorate the overall performance. However, relay transmission schemes can extend the coverage distance and offer substantial improvements over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The normalized irradiance, I, depends on both the effects of the water turbulence, I t , along with the influence of the time jitter effect, I j . Thus, the total normalized irradiance of (1), is expressed as [35][36][37][38]:…”
Section: The Underwater Channel Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The normalized irradiance, I, depends on both the effects of the water turbulence, I t , along with the influence of the time jitter effect, I j . Thus, the total normalized irradiance of (1), is expressed as [35][36][37][38]:…”
Section: The Underwater Channel Modelmentioning
confidence: 99%
“…with I l being the signal losses due to the medium's attenuation, but without loss of generality, in this work, it is assumed to be equal to unity [36][37][38]. The turbulence effect plays a very significant role in the terrestrial optical wireless links [39][40][41][42].…”
Section: The Underwater Channel Modelmentioning
confidence: 99%
“…where [8,9,17,19,29]. It should be noted that increased values of the parameter ψ {i,j} correspond to a weaker amount of misalignment-induced fading, while, w z,eq,{i,j} denotes the equivalent beam radius in the jth hop in the ith path, which is given…”
Section: Generalized Pointing Errorsmentioning
confidence: 99%
“…Consequently, it becomes evident, that MOD is of particular practical use for FSO systems design, since its value directly reveals whether the investigated system can meet the required outage specifications or not. More precisely, the MOD, T od for a specific period of time is calculated as [29,36]:…”
Section: Mean Outage Duration Estimationmentioning
confidence: 99%
“…Nevertheless, NZB pointing errors had never been examined in TOW literature, just as no method had been proposed in order to enhance the TOW outage performance and availability. Only, very recently, authors demonstrated for the first time, in [39], that a diversity method-i.e., in space, in time, or in wavelength-is an effective technique to enhance the outage performance of a typical TOW in terms of outage probability metric, by considering the joint impact of both attenuation-induced fading and misalignment-induced fading with NZB, modeled by the accurate Beckmann distribution [3,[41][42][43][44][45][46]. In basic terms, diversity refers to the consideration of multiple copies of the propagated signals in an attempt to overcome a poor transmission media state so as to reinforce the communication link's availability and robustness.…”
Section: Introductionmentioning
confidence: 99%